الأسس الفكريّة للنّحو العربيّ - البب إبراهيم; عبد الحليم فراس (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
يقوم البحث على دراسة الخطوط الرئيسة العامة التي سار عليها النّحاة في استقراء ظواهر اللّغة وتقعيدها؛ فكان لها أثرٌ في إنتاجهم وفكرهم على السواء، ومن هنا تقدّم هذه الدّراسة رؤية تحليليّة لهذه الخطوط وفق خمسة أسس متّكئةً في كلّ أساسٍ على وجهٍ فكريٍّ يجمع بين مرتكزاته، ويوضّح كيفيّة تعامله مع ظواهر اللّغة المختلفة، فأقامت الأساس الأوّل على لبنات أصول النحو العربي؛ لأنَّ الموقف من هذه الأصول كوّن موقفاً فكرياً جعل النحاة العرب ينقسمون إلى مذاهب ومدارس، وأقامت الثّاني على اعتبار المرتكزات الفكريّة الّتي تراعي النّزعة الشّكليّة للبناء اللّغويّ، وانطلقت في الثّالث من مرتكزات تمكّن من استعراض الوجوه النّحويّة ومحاكمتها عقليّاً، وبناء الحكم في الظّاهرة النّحويّة على أساس الأحكام الّتي نراها في الظّواهر الأخرى، وسعى الرّابع إلى خدمة النّصّ والوصول إلى معناه؛ في سياق الاتّساق بين النّظم والمعنى؛ وأمّا الخامس فسعى إلى إيجاد وجهٍ للظّاهرة اللّغويّة في العربيّة؛ في ضوء إمكانات علم النّحو، وعوارضه التّركيبية، وهكذا امتازت نظرة النحويٍّين بالغنى والعمق والتّنوّع، ممّا وسّع دراسة اللّغة، وأضفى عليها ألواناً من الإشراق الفكريّ في آفاق المعنى. This research depends on studying the main notions which grammarians have used in order to induce language’s phenomenon and complexity, so that it affected both their creation and thoughts. Moreover, this study presents an analytic view of these main notions according to five foundations. Each foundation depends on an intellectual side that gathers its principles and explains the method to treat different lingual phenomena. The study established the first foundation relating to the essential of Arabic syntax. Consequently, different perspectives for such fundamentals caused Arab grammarians to be divided into different schools. Moreover, the second fundamental was established with regard to intellectual principles which is considered the formal tendency to lingual structure. However, the third fundamental was able to review syntactic aspects and rationally judge it, thus making judgments of syntactic phenomenon according to other phenomenon rules. The fourth fundamental’s purpose was to study the text and conclude its meaning in sequence of consistency between system and meaning. Finally, the fifth fundamental’s purpose was the discovery of lingual phenomenon’s aspects in the Arabic language relying on the prospects of syntax and its structural symptoms. Therefore, the perspective of grammarians was distinguished by richness, depth, and diversity, which in turn develops the study of language adding to it a kind of intellectual brightness.